Pengaruh Citra Merek, Persepsi Harga dan Lokasi Terhadap Keputusan Pembelian Kopi Kenangan Cipayung - Christi Febry Linawati; Bambang Ns (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Increasingly competitive competition, Kopi Kenangan cafes must innovate to keep up with the times. In the case of Kopi Kenangan Cipayung, the decisions made by customers regarding purchases can affect the company's profits, so it is very important for business. This study aims to discuss the impact on brand image (X1), price perception (X2), and location (X3) as intervening variables on purchasing decisions (Y) at Kopi Kenangan Cipayung. This study uses anti-survey arguments. The accidental sampling method was used to collect (n=100) individuals who had purchased Kenangan Cipayung coffee. Primary data collected directly from the respondents is used to analyze multiple regression analysis. Based on research findings, purchasing decisions on Kopi Kenangan Cipayung are influenced by Brand Image. It is underlined that the perception of price and location has an impact on purchasing decisions.